Improving Heat Exchanger Network Design of a Revamped Chemical Plant - Zulfan Adi Putra (Universitas Pendidikan Indonesia, 2017)
Pinch analysis has been known as one of the tools for smart energy management. This technique has successfully been applied in more than three decades in various industries. Here, the purpose of this study was to describe how to use pinch analysis for improving heat exchanger network design of a revamped chemical plant. In a revamping project of a chemical plant, the pinch analysis is applied to find a better design. The analysis reveals that the revamped case can be further improved to achieve more energy saving. This is done by applying one of the golden rules in pinch analysis, which is not to transfer heat across the pinch. The proposed solution is rather simple and straightforward, leading to only few months of payback period and 165 k€ per annual saving.